Corruption in Nepal: An analytical Study - Shah, R. K. (Economic Journal of Nepal, 2017)
Nepal is the 122nd least corrupt nations out of 175 countries throughout the world according to the 2017 'Corruption Perceptions Index (CPI)' reported by Transparency International. Corruption Rank in Nepal averaged 127. 64 from 2004 until 2017 A.D., reaching an all time high of 154 in 2011 and a record low of 90 in 2004. Various cases of VAT fraud, massive irregularities in the distribution of relief materials of earthquake victims and the government's failure to control the artificial increase of fuel and basic goods, prices after Madhesh agitation and crisis in Nepal-India trade relation has evidenced that corruption in Nepal has becoming systemic. However, no study is undertaken to estimate the magnitude of corruption. Therefore, along with the promulgation of the Federal Democratic Republic Constitution of Nepal, 2015AD, time has come to conduct a nationwide survey to estimate the magnitude of corruption in Nepalese economy and identify the measures to control it. This study has analyzed the historical trends of corruption and economic growth as well as conceptual and theoretical issues of corruption. The main objective of the study is to analyze the determinants of corruption in Nepal. In order to obtain valid useful data about corruption, academic research has been the main sources of information in this study. The objective of the study has to analyze the trend, extend and explore the determinants of corruption in Nepal. Both inductive and descriptive approach has been adopted for methodology. The corruption data have been taken from Transparency International (TI). ADB and Economic Surveys of Nepal have been taken the data for other variables.